Shut Up and Play, or Get Out: A Pedagogy of Gendered Digital Identities in Video Gaming - Schmitz, Kelsey Catherine (Université d'Ottawa / University of Ottawa, 2018)
This research project is an answer to the question, “What is the trouble with Gender and Gaming?” Distinguishing between sex and gender, the research examines how players learn to participate in gaming culture through a gendered lens and explores the voices of participant gamers who are learning and dealing with gendered violence and sexism in video games. Specifically, I examined the complicated nature of power, gendered representations/performances and language in gaming. To accomplish this, I used a poststructural feminist theory that I call ‘theory of disruption,’ which utilizes Butler’s (1991) theories on gender performance, Foucault’s (1978) concept of the docile body, and Harraway’s (1991) theory of disruption through the metaphor of the cyborg. Methodologically, I used digital ethnography, where I took on the role of participant-researcher by examining and analyzing my experiences as a video game player, on the one hand, and played with and interviewed 12 avid North American video gamers, all of whom are English speakers, including 8 women and 4 men, on the other. In analyzing my own and the participants’ narratives, gendered violence and sexual violence perpetuated within the context of gaming was deemed as a major deterrent for self-identified female gamers, often leaving them disconnected from the gaming community, and at times driving them to stop playing online games completely. In the case of female gamers, I show, they begin gaming already orienting their performance around a male narrative and in a male-dominated space. Throughout the thesis, we see that the trouble with gender and gaming is how gender is performed in games: cultural limitations, as well as design limitations influenced by culture, restrict players to the point where performativity (i.e. the pattern of gender performance) morphs into gender norms. These norms, I also show, are not left to perpetuate. In many cases, they are disrupted, subverted, dismissed or outright ignored. Nonetheless, I conclude, all gamers, male or female, have to negotiate gendered identities and their storylines as represented and made available by game designers. Approached as a ‘null curriculum’ (Eisner, 1985), video gaming is a site where most people, but particularly young people, invest in their identities and desires, thus turning it into a learning site. Here, particular representations and gendered norms and behaviours are learned. Pedagogically, I therefore conclude, we need to critically engage with it and show its creative as well as its ‘other’ (especially when it comes to female representation) side. Membership to the gaming community, it seems, is open to anyone with a gaming system and a desire to log into play; but if those community members were more attuned to how their actions, words, and conversations impact their greater community, perhaps we would begin to see a version of the gaming culture that is safer and more open to all.
Keywords: Digital Education; Gender; Video Games; Sexual Violence/Language